Tinjauan Yuridis Terhadap Pembatalan Peraturan Daerah Provinsi di Indonesia - Minolah Minolah (Fakultas Hukum, Universitas Islam Bandung, 2011)
The case of this thesis is how the regulation of judicial local act authority in Indonesia. And how the implementation of 185 articel of act number 32/2004 about the local government. And what the implication of 144 article of act number 32/2004 about the local government and what the law instrument is appropriate with province act strike down. From the conceptual approach and statute approach, we can make conclusion that the judicial of local act could be done from two authority, judicial review with supreme court and executive review with president c.q the internal minister, the stating of local act in 185 article of act 32/2004, can’t to implementing, until the mixtime a long 30 days to stating the local act is not impelemented. And the executive regulation as the instrument to strike down the local act is wrong. Because of that, recommended to make harmonization or synchronization between executive and Supreme Court sincronisation authority. And revise 185 article of act 32/2004 and the law instrument to strike down a province act is president decition.